Deteksi Umur Pubertas Muncak (Muntiacus muntjak muntjak) Betina Berdasarkan Analisis Metabolit Estrogen dan Progesteron pada Feses (THE AGE OF PUBERTY DETECTION IN FEMALE BARKING DEER (MUNTIACUS MUNTJAC MUNTJAC) BASED ON FAECAL ESTROGEN AND PROGESTERONE A - Pudjirahaju, Asri; Supriatna, Iman; Agungpriyono, Srihadi; Agil, Muhammad (Jurnal Veteriner, 2015)
Knowledge and information about the age of puberty in muntjac (Muntiacus muntjac muntjac) isindispensable to the interests of females breeding in conservation efforts. The aims of this study were todetermine the age of puberty and age at first mated females muntjac kept in captivity through the analysisof estrogen and progesterone metabolites in feces. This study used 155 fecal samples that were collectedfrom three female muntjacs. Sample collection was began when muntjac aged three months, four monthsand six months. Total of 10-20 g fecal samples were collected every 2-4 days. Analysis of steroid hormonemetabolites was performed by using enzyme immunoassay (EIA) method with specific antibodies.Determination of the age of puberty was based on the appearance of the first time estrus and ovulation,which was indicated by the appearance of the highest estrogens secretion, on hormone metabolites profile.Hormone metabolites data then were tabulated in the average and standard deviations were presentedwith graphs and analyzed descriptively. The results showed that the age of puberty detection based onanalysis of the estrogens and progesterone metabolite in the feces can be applied in muntjac. Muntjacfemales kept in captivity flats reached puberty at age 5±1 month or 4-6 months range. It is recommendedthe first mated in the muntjac is at least after the female experienced two period of oestrous or has reachedat age of six months.
Keywords: M. m. muntjac, puberty, total estrogen, Pg-diol